Paul, Salomé. Marina Carr and Greek Tragedy: Feminist Myths of Monstrosity. New York and London: Routledge, 2024 - Witzany Hutková, Klára (FOCUS: Papers in English Literary and Cultural Studies, 2025)
The review examines Salomé Paul’s Marina Carr and Greek Tragedy: Feminist Myths of Monstrosity, highlighting its exploration of Carr’s engagement with Classical sources through feminist and intertextual perspectives. It emphasizes Paul’s analysis of Carr’s reworking of female figures, myth, and genre, as well as her concept of “epic tragedy.” The review underscores the monograph’s contribution to both Carr scholarship and Classical studies, particularly in its focus on gender, adaptation, and the transformation of tragic form.